Coating agent, modified graphite material, preparation method and application thereof

By using coal asphalt, petroleum asphalt and thermosetting resin coating agents to form a uniform shell, the problem of poor rate performance of the negative electrode material of lithium-ion battery is solved, and modified graphite materials with high rate performance and high specific capacity are achieved, which simplifies the The preparation process and the coating agent content was reduced.

CN114388806BActive Publication Date: 2024-12-13NINGBO SHANSHAN NEW MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111673670.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2024-12-13
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

The rate performance of existing lithium-ion battery negative electrode materials is poor, which is difficult to meet the needs of fast charging, and the preparation process is complex and compatibility is difficult to control.

Method used

A coating agent is used, including coal asphalt, petroleum asphalt and thermosetting resin. The softening point of the solute is 250-300°C, and the mass ratio of the solvent to the solute is 1: (0.01-0.28). A uniform graphite surface is formed by carbonization treatment. The housing improves the fast charging performance and discharge capacity of the material.

Benefits of technology

The high-rate performance and first-time efficiency of lithium-ion battery materials are achieved, the high specific capacity is maintained, and the preparation method is simple and the coating agent content is low, avoiding the problem of unevenness of the coating layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114388806B_ABST
    Figure CN114388806B_ABST
Patent Text Reader

Abstract

The present invention discloses a coating agent, a modified graphite material, and a preparation method and application thereof. The coating agent comprises a solvent and a solute; the solute is one or more of coal tar pitch, petroleum asphalt and a thermosetting resin; the softening point of the solute is 250-300°C; the mass ratio of the solvent to the solute is 1:(0.01-0.28). The modified graphite material prepared by using the coating agent of the present invention has higher rate performance, higher discharge capacity and first efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coating agent, a modified graphite material, and a preparation method and application thereof. Background Art

[0002] With the development of the new energy industry, the performance of materials has reached a bottleneck period. To break through the performance limitations, the negative electrode materials of lithium-ion batteries have gradually developed from single components to composite materials. The main form of the negative electrode material of a single lithium-ion battery is particles. Since the material is prepared using a top-down method, it has a certain particle size distribution and the particle morphology is also rough.

[0003] The commercially available lithium-ion negative electrode materials include carbon materials, silicon materials, and lithium carbonate, among which carbon materials account for the largest proportion. Carbon materials have developed from the original single components, such as natural graphite, artificial graphite, and intermediate carbon microspheres, to carbon-carbon composite materials, that is, the core is natural graphite or artificial graphite, and the shell is soft, hard, or hard carbon.

[0004] The capacity of existing single-component commercial lithium-ion negative electrode carbon materials has exceeded 360 mAh per gram, which is very close to the theoretical specific capacity of carbon materials of 372 mAh per gram, and there is little room for capacity improvement; commercial lithium-ion batteries are widely used, and the comprehensive requirements for performance are also increased, such as fast charging performance, high and low temperature performance, and rate performance.

[0005] The rapid application of new materials is to make small adjustments to the original process preparation path. In the case that liquid electrolyte lithium-ion batteries have not been replaced on a large scale, the preparation of negative electrode materials for pole pieces still needs to go through steps such as batching, beating, baking, and cutting. In the battery system, the diaphragm and electrolyte are in direct contact with the negative electrode material, and the electrolyte will form SEI (solid electrolyte interface membrane) with the surface of the negative electrode material. This SEI determines the compatibility of the negative electrode material. With the development of EV power batteries, in addition to the requirements for long battery life, people also hope to be able to complete 50% Soc replenishment in a short time (20-30min) during use, and be able to complete the last distance of power; so the demand for fast-charging batteries is getting higher and higher, so fast-charging graphite negative electrode materials are needed to match. At present, many graphite materials on the market are prone to lithium precipitation on the negative electrode surface when charging at a high rate, which has a great impact on the safety of the battery cell. Therefore, how to improve the fast charging capability of the battery cell while ensuring safety and performance has become a problem that needs to be solved urgently.

[0006] Composite carbon-carbon materials can improve the high and low temperature performance and rate performance of lithium-ion batteries. In particular, the shell structure can improve the processing performance and electrolyte compatibility. The shell structure can also improve the surface problems of the core structure, and have better performance improvement. The shell of existing carbon-carbon composite materials is mainly soft carbon and hard carbon. The existing commercial single coating agent can only prepare one carbon material structure, and the multi-component coating agent has compatibility issues.

[0007] For example, Chinese patent document CN112670469A discloses a coating agent, which includes coumarone resin and washing oil in a mass ratio of (1-3):1, wherein the softening point of the coumarone resin is 80-90°C. The coating agent prepared by this formula belongs to the soft carbon type coating agent with poor rate performance. Chinese patent document CN112768691A discloses a coating agent, which includes a solute, a solvent and an auxiliary agent; the solvent is one or more of coal tar, petroleum asphalt and petroleum resin; the auxiliary agent includes a cross-linking agent. This patent uses multiple reagents and the preparation process is complex and difficult to control. At present, the above technical problems have yet to be solved. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the defect of poor rate performance of the coating agent in the prior art when preparing the modified graphite material, and provide a coating agent, a modified graphite material and a preparation method and application thereof. The modified graphite material prepared by the coating agent of the present invention has higher rate performance, higher discharge capacity and first efficiency, and the preparation method is simple. At the same time, the percentage of the mass of the shell in the modified graphite material prepared by the coating agent of the present invention to the total mass of the modified graphite material is small, and it can have a higher specific capacity in the long-term use of lithium batteries.

[0009] The present invention provides a coating agent, which includes a solvent and a solute;

[0010] The solute is one or more of coal tar, petroleum tar and thermosetting resin;

[0011] The softening point of the solute is 250-300°C;

[0012] The mass ratio of the solvent to the solute is 1:(0.01-0.28).

[0013] In the present invention, those skilled in the art know that the coating agent generally refers to a coating agent formed on the surface of graphite.

[0014] In the present invention, the coating agent is preferably composed of a solvent and a solute.

[0015] In the present invention, the mass ratio of the solvent to the solute is preferably 1:(0.05-0.18), for example, 1:0.08, 1:0.1, 1:0.12 or 1:0.15.

[0016] In the present invention, the solvent may be conventional in the art, preferably a petroleum-based solvent or a recovered product thereof.

[0017] The recovered product of the petroleum-based solvent may have a meaning commonly understood in the art, such as the recovered product of the petroleum-based solvent produced during petrochemical processing and graphite negative electrode processing, or the petroleum-based mixture condensed during the condensation process.

[0018] The petroleum-based solvent preferably includes one or more of anthracene oil, anthracene oil recovery, naphthalene oil, wash oil, ethylene tar, catalytic cracking slurry, atmospheric residue oil and vacuum residue oil, preferably anthracene oil and / or wash oil.

[0019] In the present invention, the density of the solvent is preferably 0.99 to 1.15 g / cm 3 , for example 1.03 g / cm 3 , 1.05g / cm 3 , 1.08g / cm 3 or 1.1 g / cm 3 .

[0020] In the present invention, those skilled in the art know that the solvent is generally in liquid state at normal temperature and pressure.

[0021] In the present invention, those skilled in the art know that when the softening point of the solute is between 250° C. and 300° C., the solute is generally in a solid state at normal temperature and pressure.

[0022] In the present invention, the softening point of the solute is preferably 260-290°C, such as 265°C, 275°C or 280°C.

[0023] In the present invention, the solute is preferably one or more of petroleum asphalt, polyester resin and epoxy resin, more preferably petroleum asphalt and polyester resin, or petroleum asphalt and epoxy resin. It was found during the experiment that the combination of specific types of solutes can obtain lithium battery materials with better fast charging performance.

[0024] Wherein, when the solute is petroleum asphalt and polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is preferably (1-5):1, such as 2:1 or 4:1.

[0025] Wherein, when the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is preferably 3:(1-3), for example, 3:2.

[0026] In the present invention, the coal pitch may be conventional in the art, preferably coal tar pitch.

[0027] In the present invention, the petroleum asphalt can be conventional in the art, and is preferably spinnable oxidized asphalt.

[0028] In the present invention, the thermosetting resin may be conventional in the art, and preferably includes polyester resin and / or epoxy resin.

[0029] In the present invention, the relative molecular weight of the thermosetting resin is preferably 10,000 to 3,000, such as 15,000, 20,000 or 25,000.

[0030] In the present invention, the relative molecular weight of the polyester resin is preferably 10,000 to 20,000.

[0031] In the present invention, the relative molecular weight of the epoxy resin is preferably 15000-25000.

[0032] In a specific embodiment of the present invention, the coating agent is composed of the following components: petroleum asphalt and anthracene oil, the mass volume ratio of the petroleum asphalt to the anthracene oil is 0.1 kg / L, and the density of the anthracene oil is 1.05-1.1 g / cm 3 , the softening point of the petroleum asphalt is 250°C.

[0033] In a specific embodiment of the present invention, the coating agent is composed of the following components: a solute and a solvent, the solute is petroleum asphalt and a polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is 4:1, the solvent is anthracene oil recovery material, the softening point of the petroleum asphalt is 280°C, the softening point of the polyester resin is 260-270°C, the relative molecular weight of the polyester resin is 10,000-20,000, and the mass volume ratio of the solute to the solvent is 0.1 kg / L.

[0034] In a specific embodiment of the present invention, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:1, the solvent is washing oil, the softening point of the petroleum asphalt is 250°C, the softening point of the epoxy resin is 265-275°C, and the density of the washing oil is 1.03-1.05 g / cm 3 , the mass volume ratio of the solute to the solvent is 0.08 kg / L.

[0035] In a specific embodiment of the present invention, the coating agent is composed of the following components: the coating agent is composed of the following components: a solute and a solvent, the solute is petroleum asphalt and a polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is 2:1, the solvent is anthracene oil recovery material, the softening point of the petroleum asphalt is 280°C, the softening point of the polyester resin is 260-270°C, the relative molecular weight of the polyester resin is 10,000-20,000, and the mass volume ratio of the solute to the solvent is 0.12 kg / L.

[0036] In a specific embodiment of the present invention, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:2, the solvent is washing oil, the softening point of the petroleum asphalt is 250°C, the softening point of the epoxy resin is 265-275°C, and the density of the washing oil is 1.03-1.05 g / cm 3 The mass volume ratio of the solute to the solvent is 0.1 kg / L.

[0037] In a specific embodiment of the present invention, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and a polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is 4:1, the solvent is anthracene oil recovery material, the softening point of the petroleum asphalt is 250°C, the softening point of the polyester resin is 260-270°C, the relative molecular weight of the polyester resin is 10,000-20,000, and the mass volume ratio of the solute to the solvent is 0.1 kg / L.

[0038] In a specific embodiment of the present invention, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:1, the solvent is washing oil, the softening point of the petroleum asphalt is 280°C, the softening point of the epoxy resin is 265-275°C, and the density of the washing oil is 1.03-1.05 g / cm 3 , the mass volume ratio of the solute to the solvent is 0.08 kg / L.

[0039] In the present invention, the coating agent can be prepared by a conventional preparation method in the art, generally by uniformly mixing the solute and the solvent.

[0040] Preferably, the solute is added into the solvent and then the mixing is performed.

[0041] Wherein, the mixing is preferably performed under an inert atmosphere.

[0042] The mixing temperature is preferably 50-90°C, such as 60°C, 70°C or 80°C.

[0043] The mixing is preferably performed by stirring.

[0044] The invention also provides a method for preparing a modified graphite material, which comprises the following steps: subjecting a mixture of the coating agent and graphite to carbonization treatment to obtain the modified graphite material.

[0045] In the present invention, the mass ratio of the coating agent to the graphite is preferably (9-12):100, for example, 10:100.

[0046] In the present invention, the D50 particle size of the graphite is preferably 11 to 17 μm, such as 14 to 16 μm. The coating agent can form a more uniform coating layer by mixing with graphite particles of a specific particle size and then undergoing the carbonization treatment.

[0047] In the present invention, the graphite can be conventional in the art, for example, artificial graphite and / or natural graphite. Those skilled in the art know that when the graphite is artificial graphite and natural graphite, it is generally called composite graphite.

[0048] The artificial graphite can be purchased from Ningbo Shanshan New Material Technology Co., Ltd., or can be prepared by the following preparation method, including subjecting the raw material of the artificial graphite to heat treatment and graphitization.

[0049] The raw material of the artificial graphite may be one or more of carbon fiber, pyrolytic carbon and petroleum coke, such as petroleum coke.

[0050] The temperature of the heat treatment may be 550-650°C.

[0051] The graphitization temperature is preferably 2800-3200°C, for example 3000°C.

[0052] In the present invention, those skilled in the art know that the mixture of the coating agent and graphite generally refers to the surface of the graphite attached by the coating agent.

[0053] In the present invention, the preparation method of the mixture of the coating agent and graphite can be conventional in the art, and generally the coating agent is mixed with the graphite.

[0054] The mixing is generally carried out in a fusion machine at a temperature of 20 to 30°C.

[0055] The rotation speed of the fusion machine is preferably 600-800 r / min, for example 700 r / min.

[0056] In the present invention, the temperature of the carbonization treatment is preferably 1050°C to 1250°C, such as 1100°C or 1150°C.

[0057] During the research and development process, the inventors discovered through many experiments that by selecting a specific type of solute and combining it with a petroleum-based solvent or its recycled product, and then combining the two in a specific mass ratio, a mixture of the coating agent and graphite can form a uniformly coated shell on the surface of the graphite after carbonization treatment, thereby improving the fast charging performance and maintaining better discharge capacity and initial efficiency.

[0058] Moreover, the content of the coating agent finally formed on the graphite surface of the present invention is low, and the lithium-ion battery has a high specific capacity during long-term use. It should be noted that when preparing a coating agent with a core-shell structure, those skilled in the art may worry that the hard carbon content added to the coating agent is too small, resulting in an uneven coating layer during the formation of a shell layer on the graphite, which generally increases the proportion of solute. For example, in the modified graphite materials obtained by the above two prior arts, the mass proportion of solute in the coating agent is relatively large. Such a ratio will form more coating agents on the surface of the graphite, and the proportion of coating agents in the obtained modified graphite material is relatively large. In fact, uneven coating often occurs, which will affect the electrochemical properties of the lithium battery, and especially cause a decrease in specific capacity during long-term use.

[0059] The present invention also provides a modified graphite material, which is prepared by the above preparation method.

[0060] The invention also provides an application of the modified graphite material in a lithium ion battery.

[0061] The present invention also provides a lithium ion battery, wherein the electrode material of the lithium ion battery comprises the modified graphite material.

[0062] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention. In the present invention, the room temperature is 20-30°C.

[0063] The reagents and raw materials used in the present invention are commercially available.

[0064] The positive and progressive effect of the present invention is that the modified graphite material prepared by using the coating agent of the present invention has higher fast charging performance, higher discharge capacity and first efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is a scanning electron microscope image of the modified graphite material obtained in Example 1.

[0066] Figure 2 This is a scanning electron microscope image of the modified graphite material prepared in Example 2.

[0067] Figure 3 This is a scanning electron microscope image of the modified graphite material prepared in Example 3.

[0068] Figure 4 This is a comparison chart of the fast charging performance of lithium batteries made from modified graphite materials in Example 1, Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0069] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0070] The sources of the raw materials in the following examples and comparative examples are as follows:

[0071]

[0072]

[0073] The artificial graphite used in the following Examples 1 to 7 and Comparative Examples 1 to 2 has a D50 particle size of 14 to 16 μm and is prepared by the following method: it is obtained by heat treatment and graphitization of petroleum coke, the heat treatment temperature is 550 to 650° C., and the graphitization temperature is 3000° C.

[0074] Example 1

[0075] 1. Preparation of coating agent

[0076] (1) Place 10 L of anthracene oil in an inert container;

[0077] (2) adding 1 kg of petroleum asphalt having a softening point of 250° C. to the anthracene oil;

[0078] (3) using a magnetic stirrer to stir evenly at 60°C;

[0079] (4) Package the stirred liquid.

[0080] 2. Preparation of modified graphite materials

[0081] The coating agent and artificial graphite prepared above are mixed in a fusion machine in a mass ratio of 10:100. The mixing conditions are air atmosphere and room temperature. The speed of the fusion machine is 700r / min. The fusion time is 120s. The fusion process can achieve uniform dispersion and coating of the coating agent and artificial graphite. The coated artificial graphite material is heated in a roller kiln under the protection of an inert atmosphere, kept at a constant temperature of 1150°C for 6h, and then forced to cool to obtain a modified graphite material.

[0082] Example 2

[0083] 1. Preparation of coating agent

[0084] (1) placing 100 L of anthracene oil recovery material in a container with an inert atmosphere;

[0085] (2) adding 8 kg of petroleum asphalt with a softening point of 280° C. and 2 kg of polyester resin to the anthracene oil recovery;

[0086] (3) stirring uniformly at 80°C using a propeller stirrer;

[0087] (4) Package the stirred liquid.

[0088] 2. Preparation of modified graphite materials

[0089] The preparation of the modified graphite material in this embodiment 1 is the same as that in embodiment 1, except that the carbonization constant temperature is 1100°C.

[0090] Example 3

[0091] 1. Preparation of coating agent

[0092] (1) Place 1000L of wash oil in an inert container;

[0093] (2) adding 60 kg of petroleum asphalt with a softening point of 250°C and 20 kg of epoxy resin to the above wash oil;

[0094] (3) stirring evenly at 70°C using a turbine stirrer;

[0095] (4) Package the stirred liquid.

[0096] 2. Preparation of modified graphite materials

[0097] The preparation of the modified graphite material in this embodiment 1 is the same as that in embodiment 1, except that the carbonization constant temperature is 1200°C.

[0098] Example 4

[0099] The difference from Example 2 is that when preparing the coating agent, the mass of the polyester resin added is 4 kg, and the rest of the formula and preparation process are the same as Example 2.

[0100] Example 5

[0101] The difference from Example 3 is that when preparing the coating agent, the mass of the epoxy resin added is 40 kg, and the rest of the formula and preparation process are the same as Example 3.

[0102] Example 6

[0103] The difference from Example 2 is that the softening point of the petroleum asphalt added when preparing the coating agent is 250°C, and the rest of the formula and preparation process are the same as Example 2.

[0104] Example 7

[0105] The difference from Example 3 is that the softening point of the petroleum asphalt added when preparing the coating agent is 280°C, and the rest of the formula and preparation process are the same as Example 3.

[0106] Comparative Example 1

[0107] In this comparative example 1, only ethylene tar is used as the coating agent. The rest of the preparation process of the coating agent is the same as that of Example 1, and the preparation of the modified graphite material is the same as that of Example 1.

[0108] Comparative Example 2

[0109] In this comparative example, only anthracene oil is used as a coating agent to coat graphite for carbonization treatment, and the rest is the same as in Example 1.

[0110] Effect Example 1

[0111] 1. Performance test of modified graphite materials

[0112] The modified graphite materials prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were tested as follows according to the conventional techniques in the art:

[0113] (1) The modified graphite materials prepared in Examples 1 to 3 were tested using a scanning electron microscope Phenom XL according to conventional testing methods in the art. The test results are as follows: Figure 1 As shown. Figures 1 to 3 It can be seen that the modified graphite material of the present invention is a uniformly coated graphite material.

[0114] (2) The particle size of the modified graphite material was tested using a laser particle size distribution analyzer MS3000; the test results are shown in Table 1.

[0115] (3) The tap density of the modified graphite material was tested using a tap compactor TF-100B. The test results are shown in Table 1 below.

[0116] (4) The specific surface area of ​​the modified graphite material was tested using a specific surface area meter NOVATouch2000; the test results are shown in Table 1.

[0117] (5) The compaction density of the modified graphite material was tested using an FT-100F automatic powder compaction density tester; the test results are shown in Table 1. During the compaction density test, the modified graphite material was compacted twice.

[0118] (6) The true density of the modified graphite material was tested using the true density meter AccuPycⅡ1340.

[0119] 2. Electrical performance test

[0120] The modified graphite material, conductive carbon black SP, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR prepared in Examples 1 to 7 and Comparative Examples 1 to 2 were weighed according to a mass ratio of 94.5:1.5:1.5:1.5, respectively, and stirred evenly in water to form a negative electrode slurry, which was evenly coated on a copper foil using an applicator, and the coated electrode was placed in a vacuum drying oven at a temperature of 110°C and vacuum dried for 4 hours, and then pressed into a sheet to form a negative electrode; the simulated button battery was assembled in a German Braun glove box filled with argon, the electrolyte was 1M LiPF6+EC∶EMC∶DMC=1∶1∶1 (volume ratio), and the metal lithium sheet was the counter electrode.

[0121] The prepared simulated button cell was tested for electrochemical performance on an American Arbin BT2000 battery tester:

[0122] (1) Discharge capacity and initial efficiency

[0123] The test conditions are: charging and discharging at a constant current of 0.1C, a charge and discharge voltage range of 0.005V-1.0V, and the discharge capacity and the first efficiency are tested according to the conventional test methods in the art. The test results are shown in Table 2 below.

[0124] Table 2

[0125]

[0126]

[0127] (2) Fast charging performance

[0128] The test conditions are as follows: the modified graphite material, conductive carbon black SP, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR prepared in Examples 1 to 7 and Comparative Examples 1 to 2 are weighed in a mass ratio of 94.5:1.5:1.5:1.5, stirred evenly in water to form a negative electrode slurry, and evenly coated on copper foil using an applicator, and the coated electrode is placed in a vacuum drying oven at a temperature of 110°C for vacuum drying for 4 hours, and then pressed into a negative electrode; the simulated button cell is assembled in a German Braun glove box filled with argon, the electrolyte is 1M LiPF6+EC∶EMC∶DMC=1:1:1 (volume ratio), and the metal lithium sheet is the counter electrode. The prepared simulated button cell is subjected to an electrochemical SOC performance test on an American ArbinBT2000 battery tester. The SOC test sets the fast charging program based on the second week lithium de-ion capacity as the standard capacity, and the 3C fast charging cut-off condition is 20 minutes. The SOC at that point is calculated by dividing the capacity of each data point recorded by the cut-off capacity. The larger the SOC value, the better the fast charging performance. The test results are shown in Table 3 below.

[0129] Table 3

[0130]

[0131]

[0132] like Figure 4 Shown is a comparison chart of the fast charging performance of lithium batteries made from modified graphite materials in Example 1, Comparative Examples 1 and 2. The unit of the horizontal axis SOC in the figure is %, and the unit of the vertical axis is dQ / dV. It can be seen from the figure that the fast charging performance of Example 1 is significantly better than that of Comparative Examples 1 and 2.

Claims

1. A coating agent, characterized in that It consists of solvent and solute; The solute is petroleum asphalt and thermosetting resin; the thermosetting resin includes polyester resin and / or epoxy resin; The softening point of the solute is 250-300°C; The solvent is a petroleum solvent or a recovered product thereof; The mass ratio of the solvent to the solute is 1:(0.08-0.12); the coating agent refers to a coating agent formed on the surface of graphite.

2. The coating agent according to claim 1, characterized in that The mass ratio of the solvent to the solute is 1:0.1 or 1:0.

12.

3. The coating agent according to claim 1, characterized in that The petroleum solvent includes one or more of anthracene oil, anthracene oil recovery, naphthalene oil, wash oil, ethylene tar, catalytic cracking slurry, atmospheric residue oil and vacuum residue oil; And / or, the density of the solvent is 0.99 to 1.15 g / cm 3 ; And / or, the solute is petroleum asphalt and polyester resin, petroleum asphalt and epoxy resin, or petroleum asphalt, polyester resin and epoxy resin.

4. The coating agent according to claim 3, characterized in that The petroleum-based solvent is anthracene oil and / or wash oil; And / or, the density of the solvent is 1.03 g / cm 3 , 1.05g / cm 3 , 1.08g / cm 3 or 1.1 g / cm 3 ; And / or, the solute is petroleum asphalt and polyester resin, or petroleum asphalt and epoxy resin.

5. The coating agent according to claim 4, characterized in that When the solute is petroleum asphalt and polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is (1-5):1; Alternatively, when the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:(1-3).

6. The coating agent according to claim 5, characterized in that When the solute is petroleum asphalt and polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is 2:1 or 4:1; Alternatively, when the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:

2.

7. The coating agent according to claim 1, characterized in that The softening point of the solute is 260-290°C; And / or, the softening point of the petroleum asphalt is 250-280°C; and / or, the softening point of the thermosetting resin is 260-275° C.; And / or, the relative molecular weight of the thermosetting resin is 10000 to 25000; And / or, the method for preparing the coating agent comprises the following steps, The solute and the solvent are mixed evenly.

8. The coating agent according to claim 7, characterized in that The softening point of the solute is 265°C, 275°C or 280°C; and / or, the softening point of the thermosetting resin is 265° C. or 270° C.; And / or, the relative molecular weight of the thermosetting resin is 15,000, 20,000 or 25,000.

9. The coating agent according to claim 8, characterized in that When the thermosetting resin is a polyester resin, the relative molecular weight of the polyester resin is 10,000 to 20,000; Alternatively, when the thermosetting resin is an epoxy resin, the relative molecular weight of the epoxy resin is 15,000 to 25,000.

10. The coating agent according to claim 7, characterized in that In the method for preparing the coating agent, the solute is added to the solvent and then mixed; And / or, the mixing temperature is 50-90°C.

11. The coating agent according to claim 10, characterized in that The mixing temperature is 60°C, 70°C or 80°C.

12. The coating agent according to claim 7, characterized in that The coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and a polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is 4:1, the solvent is anthracene oil recovery material, the softening point of the petroleum asphalt is 280°C, the softening point of the polyester resin is 260-270°C, the relative molecular weight of the polyester resin is 10000-20000, and the mass volume ratio of the solute to the solvent is 0.1kg / L; Alternatively, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:1, the solvent is washing oil, the softening point of the petroleum asphalt is 250°C, the softening point of the epoxy resin is 265-275°C, and the density of the washing oil is 1.03-1.05 g / cm 3 , the mass volume ratio of the solute to the solvent is 0.08 kg / L; Alternatively, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and a polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is 2:1, the solvent is anthracene oil recovery material, the softening point of the petroleum asphalt is 280°C, the softening point of the polyester resin is 260-270°C, the relative molecular weight of the polyester resin is 10000-20000, and the mass volume ratio of the solute to the solvent is 0.12kg / L; Alternatively, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:2, the solvent is washing oil, the softening point of the petroleum asphalt is 250°C, the softening point of the epoxy resin is 265-275°C, and the density of the washing oil is 1.03-1.05 g / cm 3 The mass volume ratio of the solute to the solvent is 0.1 kg / L; Alternatively, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and a polyester resin, the mass ratio of the petroleum asphalt to the polyester resin is 4:1, the solvent is anthracene oil recovery material, the softening point of the petroleum asphalt is 250°C, the softening point of the polyester resin is 260-270°C, the relative molecular weight of the polyester resin is 10000-20000, and the mass volume ratio of the solute to the solvent is 0.1 kg / L; Alternatively, the coating agent is composed of the following components: a solute and a solvent, wherein the solute is petroleum asphalt and epoxy resin, the mass ratio of the petroleum asphalt to the epoxy resin is 3:1, the solvent is washing oil, the softening point of the petroleum asphalt is 280°C, the softening point of the epoxy resin is 265-275°C, and the density of the washing oil is 1.03-1.05 g / cm 3 , the mass volume ratio of the solute to the solvent is 0.08 kg / L.

13. A method for preparing a modified graphite material, characterized in that: It includes the following steps: The mixture of the coating agent according to any one of claims 1 to 12 and graphite is carbonized to obtain the coating agent.

14. The method for preparing the modified graphite material according to claim 13, characterized in that: The mass ratio of the coating agent to the graphite is (9-12):100; And / or, the D50 particle size of the graphite is 11 to 17 μm; And / or, the graphite includes artificial graphite and / or natural graphite; And / or, the mixture of the coating agent and the graphite refers to a mixture formed by the coating agent adhering to the surface of the graphite; And / or, the method for preparing the mixture of the coating agent and the graphite comprises the following steps: mixing the coating agent with the graphite; And / or, the temperature of the carbonization treatment is 1050°C to 1250°C.

15. The method for preparing a modified graphite material according to claim 14, characterized in that: The mass ratio of the coating agent to the graphite is 10:100; And / or, the D50 particle size of the graphite is 14 to 16 μm; And / or, the method for preparing artificial graphite comprises the following steps: subjecting the raw material of artificial graphite to heat treatment and graphitization treatment; And / or, in the method for preparing the mixture of the coating agent and the graphite, the mixing temperature is 20 to 30° C.; And / or, in the method for preparing the mixture of the coating agent and the graphite, the mixing speed is 600-800 r / min; And / or, the temperature of the carbonization treatment is 1100°C or 1150°C.

16. The method for preparing the modified graphite material according to claim 15, characterized in that: The raw material of the artificial graphite is one or more of carbon fiber, pyrolytic carbon and petroleum coke; And / or, in the method for preparing artificial graphite, the temperature of the heat treatment is 550-650°C; And / or, in the method for preparing artificial graphite, the graphitization temperature is 2800-3200°C; And / or, in the method for preparing the mixture of the coating agent and the graphite, the mixing rotation speed is 700 r / min.

17. The method for preparing a modified graphite material according to claim 16, characterized in that: The raw material of the artificial graphite is petroleum coke; And / or, in the method for preparing artificial graphite, the graphitization temperature is 3000°C.

18. A modified graphite material, characterized in that: It is prepared by the preparation method according to any one of claims 13 to 17.

19. Use of the modified graphite material according to claim 18 in a lithium ion battery.

20. A lithium ion battery, characterized in that: The electrode material of the lithium-ion battery comprises the modified graphite material as claimed in claim 18.

Citation Information

Patent Citations

  • Coating agent, modified graphite material, preparation method and application of modified graphite material, and lithium ion battery

    CN112670469A

  • Natural graphite-based modified composite material and preparation method thereof, and lithium ion battery comprising modified composite material

    CN108063229A

  • Coating agent, coated modified graphite negative electrode material, preparation method and application of coated modified graphite negative electrode material, and lithium ion battery

    CN112768691A